Aqueous media ultra-sensitive detection of antibiotics via highly stable luminescent 3D Cadmium-based MOF. (2nd November 2021) - Asad, Muhammad; Wang, Shan; Wang, Qian-You; Li, Lin-Ke; Anwar, Muhammad Imran; Younas, Ayesha; Zang, Shuang-Quan
Abstract : A novel Cd-based MOF shows high sensitivity ( K sv ∼ 10 6 M −1 ) and selectivity (μM level) towards antibiotics was presented. Abstract : Antibiotics are a kind of chief contaminants in water, which have severe effects on the environment and mortal health. The achievement of easy and promising methods for antibiotic sensing is vastly desirable but still challenging. Fast, facile, and dependable recognition of these hazardous antibiotic contaminants by luminescent probes have importance in environmental safety. Herein, we synthesized a highly luminescent cadmium-based MOF [Cd(BPDC)(BP4VA)·2DMF] n (1 ) using 9, 10-bis(( E )-2-(pyridin-4-yl)vinyl)anthracene (BP4VA) and biphenyl-4, 4′-dicarboxylic acid (H2 BPDC) as ligands. The as-prepared compound is highly stable in water within a wide range of pH (2–12). The attained LOD values up to μM level shows higher selectivity towards antibiotics. 1 exhibits attractive detection sensitivity ( K sv = 10 6 M −1 ) towards selected antibiotics among earlier reported MOF-based luminescent probes.